Hubungan Pembelajaran Daring dengan Tingkat Stres Akademik Saat Pandemi COVID-19 pada Mahasiswa Fakultas Kedokteran. - Saudale, Sarah Grace Neljti Wilhelmina Emmanuela; Folamauk, Conrad Liab Hendricson; Trisno, Idawati; Handoyo, Nicholas Edwin (Cendana Medical Journal, 2023)
Background : The outbreak of COVID-19 ended up as a massive global pandemic, caused government to determine lockdown and social distancing to cut the transmission. People are forced to work and study from home. The change of study method from face to face to online learning caused the study to be ineffective. These problems can cause academic stress in medical student. Demands and diffuculties during pandemic can cause downfall of academic achievement, concentration in study, failure in study and psychology disorders. Objective : To determine the correlations of online learning and academic stress during COVID-19 pandemic in medical student. Methods : This is a research is quantitative analytic using cross sectional that conducted to preclincal student, faculty of medicine nusa cendana university. The data were collected using the questionaire of online studying and academic stress from previous study based on theory. The sampels were chosen using stratified random sampling methods with 157 samples from 2018, 2019 and 2020 batch that fullfiling the inclusion and exclusion criteria. This study was analyzed by univariate and bivariate using the koefisien contigency test. Result and discussion : From this study it is found that out of 157 respondents, 52,9% of the respondents experienced academic stress, and 47,1% had not academic stress. Besides, it is also found that 51,6% had good level of online learning and 48,4% had very good level of online studying. The result of bivariate analyzed was p = 0,000 (p<0,05) using the keofisien contingency test shows there is a correlation between online learning and academic stress during COVID-19 pandemic on preclinical student faculty of medicine. Conclusion : The better online learning occur, the lower the level of academic stress.